2014
DOI: 10.1016/j.applthermaleng.2013.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using cool paints on energy demand and thermal comfort of a residential building

Abstract: This work studies the role of using cool paints and/or thermal insulation on the thermal behavior and energy demand of a residential building. Buildings with thermal characteristics representing both old and new constructions are considered; the results were obtained using the dynamic computer simulator ESP-r.For a case-study building in Portugal, in the summer, it was found that an increase in roof and façade value of total solar reflectance from 50 % to 92 % reduces the maximum free-float indoor temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Numerical analyses can be used to accurately predict the thermal and energy response of buildings, and thus can be used to assess the impact of energy efficient technologies and strategies (Foucquier et al, 2013). Benefits of cool roofs have been extensively investigated, and cooling savings, heating penalties, total energy balance and thermal comfort issues are presented and discussed for different building configurations and climatic conditions (Taha et al, 1988;Dias et al, 2014;Mastrapostoli et al, 2014;Zinzi, 2010), as well as the influence of ageing . Thermal response and energy efficiency of cool roof solutions were also explored by case studies, direct or by means of calibrated simulations (Akbari et al, 1997;Jo et al, 2010;Pisello and Cotana, 2014;Rosado et al, 2014;Zinzi and Fasano, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical analyses can be used to accurately predict the thermal and energy response of buildings, and thus can be used to assess the impact of energy efficient technologies and strategies (Foucquier et al, 2013). Benefits of cool roofs have been extensively investigated, and cooling savings, heating penalties, total energy balance and thermal comfort issues are presented and discussed for different building configurations and climatic conditions (Taha et al, 1988;Dias et al, 2014;Mastrapostoli et al, 2014;Zinzi, 2010), as well as the influence of ageing . Thermal response and energy efficiency of cool roof solutions were also explored by case studies, direct or by means of calibrated simulations (Akbari et al, 1997;Jo et al, 2010;Pisello and Cotana, 2014;Rosado et al, 2014;Zinzi and Fasano, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, researchers have recently focused on the role of faç ade albedo on energy demand and thermal comfort by mean of dynamic simulations [21,22]. Additionally, Zinzi et al [23] studied the effect of cool coatings applied over window shading systems demonstrating how this solution could produce non-negligible benefits in summer, reducing the solar gain entering the window.…”
Section: Introductionmentioning
confidence: 99%
“…They reached savings of up to 25% in cooling. Through the increment in the solar reflectance from 0.5 to 0.92, Dias et al [46] found a temperature reduction between 2 and 4.7 • C in constructions without thermal insulation, and between 1.2 and 3 • C in constructions with thermal insulation. Zinzi and Agnoli [36] analyzed that cold ceilings are the most effective solution for this purpose.…”
Section: Introductionmentioning
confidence: 99%